(untitled) (Al-Academy, 2018)
The researches discusses the style of acting used by (Sami Abdul-Hameed) in one of the play director (Salah AL-Kassab) production whine he called; Picturesque. The problem of this research is to discover the differences between the performance of (Sami Abdul-Hameed) in the Picturesque Theatre and the other theatre. The goal of the research is to get to know the style of acting used in (king Lear) directed by (Salah AL-Kassab). After defining the term (picturesque theatre), the researcher discusses the elements of the Visual theatre and the components of the stage picture according to (Alexander Dean) and he refers to those well-known director who had emphasized the Visual elements. Such as (Gordon Grieg) and (Franco Zeferreli). In the second part of chapter two, the researcher discusses the mechanism of the actor’s performance generally and in (Salah AL-Kassab) approach in directing of a play tends to borrow elements from deism and surrealism such as multiple focus, and not to follow the principle of cause and effect. The researcher discusses the following results; 1. There are some differences in the cultural background between the actor (Sami Abdul-Hameed) and the director (Salah AL-Kassab).2. There are some differences in the artistic approach between the actor who depends on (Stanislavski) method, and the director who belong to the trend of the art for the sake of Art. 3. (Salah AL-Kassab) in directing a play treat the actors as supper marinates. The researcher researches the following conclusions;1. To achieve the Picturesque Theatre the play director has not to use the words of the text.2. The actor in the Picturesque Theatre play as a tool by the director’s hand.3. In the Picturesque Theatre the actor has to follow all the instructions of the director.4. The actor in the Picturesque Theatre has to be more flex able and enough experience.